Ni-base superalloy powder-processed porous layer for gas cooling in extreme environments. (26th May 2016) - White, E.M.H.; Heidloff, A.; Byrd, D.; Anderson, R.; Anderson, I.
Abstract : Extreme high temperature conditions demand novel solutions for hot gas filters and coolant access architectures, i.e., porous layers on exposed components. These high temperatures, for example in current turbine engines, are at or exceeding current material limits for high temperature oxidation/corrosion, creep resistance, and, even, melting temperature. Thus novel blade designs allowing greater heat removal are required to maintain airfoil temperatures below melting and/or rapid creep deformation limits. Gas atomised Ni-base superalloy powders were partially sintered into porous layers to allow full-surface, transpirational cooling of the surface of airfoils. These powder-processed porous layers were fully characterised for surface, morphology, cross-sectional microstructure, and mechanical strength characteristics. A sintering model based on pure Ni surface diffusion correlated well with the experimental results and allowed reasonable control over the partial sintering process to obtain a specified level of porosity within the porous layer.